Leiomyoma of the Renal Vein: A Rare Tumor Presenting as a Renal Mass. (5th April 2015) - Kocak, Cengiz; Kabay, Sahin; Isler, Burak
Abstract : Leiomyomas are benign mesenchymal tumors that rarely occur in the kidney. Renal leiomyomas usually occur in the renal cortex or capsule. They are less commonly found in the muscularis propria of the renal pelvis and cortical vascular smooth muscle. In this case report, we present a 41-year-old woman who had right flank pain and detected a mass in the right kidney hilum.